‘There Were Always Men in Our House’: Gender and the Childhood Memories of Working-Class Ukrainians in Depression-Era Canada - Zembrzycki, Stacey (Labour/Le Travailleur, 2007)
Abstracts As an exploration of the childhood memories of working-class Ukrainians who grew up in Depression-era boarding houses (or houses with a few boarders) in Sudbury, Ontario, this paper treats the oral histories as the subject, not merely the method, of analysis and highlights, in particular, the gendered differences that emerge in the narratives of the men and women interviewed for this project. Moreover, this article argues that even within a politically polarized immigrant group such as the Ukrainians, where left/right, progressive/ nationalist, and secular/religious splits were so pronounced, and thus central to shaping the histories and historiographies of both camps, it was the influence of dominant gender roles rather than politics, religion, or ideology that most directly informed the differing memories of experience that men and women had of growing up Ukrainian and working class in Sudbury. In particular, this article focuses on informants’ recollections regarding three areas of activity that were part of everyday boarding house life: children’s relationships with male boarders, their domestic chores, and leisure activities.